USAHATANI IKAN SKALA RUMAH TANGGA - Ken Suratiyah (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2002)
Fish pond is the important alternative beside food crops, if water and the other natural resources are possible. So food crops farmers can generate their income by chosing fish pond-farm. This paper focusses on four main parts: labour absorption, and productivity, farmer income, profitability and household welfare level.The result of the study showed that, nevertheless most farmers were small farmers, they still regarded their main job were being food crops famers. Fish pond-farm that the farmer income, labour productivity and profitability were higher than food crops, just as part time job. By the fish pond-farm, household farmers welfare level was not be poor again. The facts showed that the role of fish pond-farm was dominant to generate househlod economic.